Exploring the inner workings of the clove hitch knot. (August 2022) - Sano, Tomohiko G.; Johanns, Paul; Grandgeorge, Paul; Baek, Changyeob; Reis, Pedro M.
Abstract: We perform a combined experimental and computational investigation of the clove hitch knot. We develop a physical model for the clove hitch by tying an elastic rod onto a rigid cylinder. In the experiments, we characterize the mechanical performance, geometry, and stability conditions of the knot. X-ray tomography allows us to characterize the 3D geometry of the rod centerline. These results also serve to validate our finite element modeling (FEM), which we use to quantify the tension profile, not accessible experimentally, along the knotted rod. We find that the clove hitch comprises alternating segments with two types of contact regions: one where the rod is in single frictional contact with the cylinder, and another with rod self-contact (where a rod segment pinches another against the cylinder). In the first region, the internal tension decays exponentially (akin to the capstan configuration), whereas, in the second, the pinch (nip) regions lead to discontinuous tension drops. We analyze these nip regions with an even simpler model system where an elastic rod is pinched between two rigid cylinders. Despite the complex contact geometry of this pinching experiment, we find that the frictional behavior of our model systems still obeys the classic Amontons–Coulomb law. Ultimately, we can regard the clove hitch knot, if tied correctly, as a functional structure enabling to drop high tension at one extremity of a filament secured onto a rigid post, all the way to zero at the other extremity. Graphical abstract: Highlights: Mechanics and geometry of physical clove hitch knots are investigated with experiments and FEM simulations. The nontrivial 3D geometry of the knot is quantified using X-ray tomography. It is found that the internal tension profile depends on the nature the contact regions. Simplified model experiments provide physical insight for future theoretical modeling.